Is soccer bad for children's heads?: Summary of the IOM Workshop on neuropsychological consequences of head impact in youth soccer (2002)
Introduction Causes of Head Injuries in Soccer Problems in Detecting Concussions Concussion Is a Brain Injury Studies of Soccer and Football Players Policy Implications Summary